Entrepreneurial intentions and capabilities on student enterprises’ performance in Malaysian higher educational institutions - Abdul Rahman, Zahari (2019)
The study of student enterprises’ performance is relative new particularly in developing countries like Malaysia. The research on this topic is very important because several past studies have mentioned unimpressive performance of student enterprises. Therefore this study is designed to measure the performance of student enterprises in Malaysian higer educational institutions because the good performance of student enterprises would facilitate the government to create job creators among university students. Although much has been done to investigate the drivers and barriers of student enterprise intentions, few studies have related outcomes of student enterprise intentions to entrepreneurial capabilities and student enterprise performance. Thus, the current study aims to examine the performance of student enterprises through three phases of enterprise process development such as the pre-founding stage (drivers and barriers to establish student enterprises) and founding stage (entrepreneurial capabilities) that effect the post-founding stage (student enterprises performance). Understanding the process is essential because it could lead to the success of student enterprises. A cluster sampling technique was used to select 369 founders of student enterprises in Malaysian public higher educational institutions, using an online survey research and analysed using partial least squares structural equation modelling (PLS-SEM). Results found support for the influence of need for achievement, innovativeness, prospensity of risk taking, and self-efficacy on student enterprise intentions. However, locus of control was unable to influence student enterprise intentions. Contrary to expectations, university roles and entrepreneurial environments were unable to support the hypothesized relationships. Perception of barriers was confirmed as having a significant negative relationship with student enterprise intentions. Furthermore, student enterprise intention positively influenced entrepreneurial capabilities and student enterprise performance. Entrepreneurial capabilities construct was found to be associated with student enterprise performance and is proved to be a mediating effect on student enterprise intentions and student enterprise performance. This study has made several theoretical contributions and provides further insights on measuring student enterprises performance, particularly in Malaysia. This research could also assist policymakers and universities to reduce the number of unemployed graduates and create a viable entrepreneurial ecosystem within the universities.